Ethnomedicinal use and biological properties of Biebersteinia multifida DC. in Uzbekistan - Islamova, Z.B.; Khojimatov, Olim K.; Bussmann, Rainer W; Islamov, Boston; Khaydarov, Khislat (Ethnobotany Research and Applications, 2026)
Background: This article presents data on the biological and morphological features, chemical composition, and traditional medicinal use of the valuable medicinal plant Biebersteinia multifida DC. in Uzbekistan. Methods: Standard methods of High-Performance Liquid Chromatography were used to study the chemical composition of the vegetative organs of Biebersteinia multifida DC. The nitrogen content was determined by the Kjeldahl method. Ethnobotanical data were collected through questionnaire surveys conducted during interviews with the local population. The survey was carried out with the informed consent of the respondents. The interviews were conducted in accordance with the International Society of Ethnobiology Code of Ethics. Results: In Uzbekistan, Biebersteinia multifida is known as Qontepar. Since ancient times, in folk medicine, a decoction prepared from the rhizomes of a plant has been used as a hemostatic agent for postpartum bleeding and stomach diseases. Infusion of the plant in milk is used for asthma, gastritis and respiratory tract diseases. In addition, B. multifida are used in traditional medicine as a medicine for diseases of the musculoskeletal system, bone fractures and skin diseases. In the laboratory, 20 types of free amino acids, 44 types of macro-, micro-, ultramicroelements, water-soluble vitamins B1, B2, B6, B9, B12, PP, C were determined from the vegetative organs of Biebersteinia multifida, and fructose, glucose, sucrose, maltose were found from carbohydrates. At the same time, the nitrogen content was determined by the Kjeldahl method, based on calculations it was found that the presence of protein in the roots, stems and leaves is 10-11%. Gallic acid was found, from flavonoids, dihydroquercitin, rutin, quercitin were found in the roots (0.0; 5.6; 2.8; 8.3 mg/kg) and in the aboveground mass (4.7; 25.2; 12.3; 11.3 mg/kg). Analysis of herbarium samples from the electronic database of the National Herbarium of Uzbekistan revealed the distribution areas of B. multifida in Uzbekistan (mountainous regions of Kashkadarya, Surkhandarya, Samarkand, Dzhizak and Tashkent regions). The largest number of finds of the species was noted in the Samarkand and Kashkadarya regions, where local residents mainly collect roots for medicinal purposes. Conclusions: Therapeutic properties of B. multifida have been identified. It was found that the biomass of the stem, leaves and root of B. multifida contains 20 types of free amino acids, 44 types of macro, micro, ultramicro elements, water-soluble vitamins B1, B2, B6, B9, B12, PP, C, from carbohydrates fructose, glucose, sucrose, maltose. The protein contents in various parts of plants are 10-11%. Keywords: Biebersteinia multifida, amino acids, stem, leaves, root, chemical composition, macro -, micro -, ultramicro - elements, vitamins, ethnobotany.